The role of NGOs in facing the social and economic repercussions of the corona pandemic in the Islamic society " A field study in Alexandria" - Ahmed, Marwa Hamdy (Journal of Language, Literature, Social and Cultural Studies, 2023)
Crises facing a given society represent a milestone in its history as they distinguish social life in its natural form, and its form after the sudden imbalance the society was exposed to. Crises may be economic, social, political, cultural, health-related or medical. They afflict a certain sector with partial paralysis, or permanent breakdown, and each crisis has its victims that are directly affected thereby, or indirectly through its various consequences. In addition, each crisis has its exploiters and beneficiaries who gain benefit therefrom and wish for its permanence. The current study attempts to monitor and analyze the role of NGOs during the different crises the Egyptian society has been exposed to, as each crisis has its impacts in different aspects of life. Among those crises, which emerged recently, is COVID-19 Pandemic. Hence, the problem of the study is to identify the nature of this disease, and the material and social support provided by these institutions in an attempt to face the various impacts of the COVID-19 pandemic, by conducting 30 interviews with NGOs founders, and their representatives within the city of Alexandria. The result has shown that these bodies sought to provide alternative sources of income for the groups that were directly affected by the crisis.